Pendekatan al-Tadarruj dalam Pembelajaran Juz Amma untuk Gen Z - Muhammad Iqbal; Ganang Prihatmoko (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Currently, Generation Z (Gen Z) faces dual challenges of syubhat (intellectual doubts) and syahwat (materialistic desires), which often lead to the abandonment of Islamic practices. This study aims to identify the educational needs of Gen Z and develop a Juz Amma teaching model based on the al-Tadarruj (gradualism) approach. Using a qualitative literature review, the research establishes a relevant educational framework for the digital era. The findings indicate that the al-Tadarruj method, rooted in the chronological revelation of the Qur'an, is highly effective in fostering Gen Z's spiritual growth through incremental change. This research proposes a three-part teaching model: 1) "Nasihat" (honest counsel) to strengthen fundamental faith; 2) Discussion-based learning to clarify maqashid (higher objectives) and resolve uncertainties; and 3) Exemplary modeling to demonstrate the practical application of Juz Amma’s morals. In conclusion, integrating al-Tadarruj into Juz Amma education provides an efficient and versatile method for Gen Z to deeply internalize spiritual concepts and cultivate Islamic character in the modern age, especially for Gen Z students at PKBM (Islamic Boarding School).